Dynamics within the CD95 death‐inducing signaling complex decide life and death of cells - Leo Neumann; Carina Pforr; Joel Beaudouin; Alexander Pappa; Nicolai Fricker; Peter H Krammer; Inna N Lavrik; Roland Eils (Molecular Systems Biology, 2010)
Abstract This study explores the dilemma in cellular signaling that triggering of CD95 (Fas/APO‐1) in some situations results in cell death and in others leads to the activation of NF‐κB. We established an integrated kinetic mathematical model for CD95‐mediated apoptotic and NF‐κB signaling. Systematic model reduction resulted in a surprisingly simple model well approximating experimentally observed dynamics. The model postulates a new link between c‐FLIPL cleavage in the death‐inducing signaling complex (DISC) and the NF‐κB pathway. We validated experimentally that CD95 stimulation resulted in an interaction of p43‐FLIP with the IKK complex followed by its activation. Furthermore, we showed that the apoptotic and NF‐κB pathways diverge already at the DISC. Model and experimental analysis of DISC formation showed that a subtle balance of c‐FLIPL and procaspase‐8 determines life/death decisions in a nonlinear manner. We present an integrated model describing the complex dynamics of CD95‐mediated apoptosis and NF‐κB signaling.